Epidemiological investigation, related factors, spatial–temporal cluster analysis of pseudorabies virus seroprevalence in Guangdong Province of China - Mengpo Zhao; Mengpo Zhao; Jing Chen; Shengjun Luo; Pian Zhang; Jinliang Chen; Chenglong Sun; Zhaowen Ren; Yanju Huang; Yanju Huang; Xiaoxiao Zhang; Hua Xiang; et al. (Frontiers in Veterinary Science)
IntroductionPseudorabies (PR) is an important zoonotic viral disease that infects a wide range of animals, including humans. In recent years, the prevalence of pseudorabies virus (PRV) has caused great economic losses to the Chinese pig industry.MethodsIn this study, 40,050 serum samples were collected from 348 pig farms in 18 districts of Guangdong Province, China, between 2017 and 2022 to investigate the seroprevalence of wild-type PRV in pigs.ResultsThe results of the enzyme-linked immunosorbent assay (ELISA) showed that seropositivity for PRV gE antibodies was 25.28% (95% CI, 24.86% to 25.71%) at the pig level. However, the seropositivity of PRV gE antibodies reached 67.44 % (95% CI, 62.14% to 71.96%) at the farm level. To identify potential factors associated with the positive rate of PRV gE antibodies, logistic regression analysis was performed, and the results showed that the seropositivity rate of PRV gE was related to factors such as geographic distribution and season. To find areas with higher PR prevalence in Guangdong Province, China, we analyzed the data using SaTScan 10.2.5 software and identified five spatiotemporal clusters of higher PRV gE antibody positivity in Guangdong Province, China, with the highest prevalence from April to June 2018.ConclusionOur study revealed seroprevalence, associated influencing factors, and spatiotemporal clustering characteristics of PRV gE antibody positivity in Guangdong Province, China, in recent years. This provides new scientific data for the development of policies related to the prevention and control of wild-type pseudorabies epidemics in Guangdong Province, China.